Avalia????o dos efeitos da atividade f??sica com jogo de videogame ativo em crian??as asm??ticas - Mendon??a, Juliana Fernandes Barreto de (2016)
Introduction: asthma is a chronic respiratory disease common in childhood, whose outstanding feature persistent inflammation of the Airways. Inflammation is active even in periods of crisis and its chronicity is associated with the action of pro-and anti-inflammatory mechanisms. These changes take these children to a pathophysiologic cycle under active and sedentary influencing on functional capacity and making the control of the disease. Objective: Assessment of the effects of physical activity with active video game in asthmatic children. Method: A cross-sectional study to date. Been evaluated 34 asthmatic children who have undergone anthropometric assessment and tetrapolar bioelectrical impedance electrical, Quality of life questionnaire (PAQLQ), Clinical asthma control (ACQ6), Pulmonary Function Test, evaluation of Respiratory Muscle Strength (FMR), the fraction of Exhaled nitric oxide (FeNO), evaluation of Peripheral Muscle Strength (1 RM) and Cardiopulmonary stress test (CST). Conclusion: The results obtained by means of physical exercise with active video game (AVG) were similar to the CST. With energy consumption in METS considered intense, we can conclude that the AVG, as well as recreational physical activities can ensure an aerobic effect the body, similar to the exercise carried out on treadmill.